Análises e Reflexões sobre a Parada do Orgulho LGBT de São Paulo e a violência contra a comunidade LGBT no Brasil - Vieira, Thalita de Moraes (Universidade Federal de São Carlos, 2021)
The present study brings a theoretical discussion about the observed contradiction that Brazil is the host of one of the biggest LGBT events in the world and, at the same time, it is a country with a high level of violence and one of the most dangerous countries for members of the LGBT community. This research is relevant because it addresses the great economic potential of the LGBT tourism segment, in addition to pointing out the social bias of the current situation of the community in Brazil. The adopted methodology was the qualitative descriptive, and a theoretical research was carried out on the LGBT community and the segment of the LGBT tourism, besides the history on the LGBT Pride Parades and specifically on the LGBT Pride Parade of São Paulo. Data on violence against the LGBT population were also analyzed. Through this research, a reflection was proposed about the importance of encouraging LGBT tourism in Brazil and the creation of public policies and initiatives to improve the security of LGBT people in the country.
Analysis and Reflections on the São Paulo LGBT Pride Parade and violence against the LGBT community in Brazil
Keywords: LGBT; Turismo LGBT; Violência; Parada LGBT; CIENCIAS SOCIAIS APLICADAS::TURISMO